Accounting standards, regulatory enforcement, and innovation - Laux, Volker; Stocken, Phillip C. (Journal of Accounting and Economics, 2018)
We examine the effects of accounting standards and regulatory enforcement on entrepreneurial innovation and social welfare. When the entrepreneur issues a financial report that violates the accounting standards, a regulatory agency may detect the violation and bring charges. We find that when regulatory penalties are relatively insensitive to the magnitude of the violation, optimal standards are sufficiently low that they induce full compliance, and increase as the intensity of enforcement increases. In contrast, when regulatory penalties are sensitive to the magnitude of the violation, optimal standards induce non-compliance and decline as the intensity of enforcement increases.